Development of Innovative Teaching Materials through Scientific Approach - Suarman, Suarman; Hendripides, Hendripides; Hikmah, Nurul (Journal of Educational Sciences, 2018)
This study aims to develop teaching materials of economiclearning assessment through scientific approach. The research used Researchand Development (R&D) method that developed by Thiagarajan, Semmel,and Semmel that includes defining phase, design stage, and developmentstage. Data were collected from the assessment of three experts through anexpert validation sheet and responses from 40 students through studentresponse questionnaire. Data analysis using quantitative descriptivetechnique. The result of the research showed that the teaching materials aresuitable for learning through the scientific approach on the course of theEconomic Learning Assessment. of material experts with an average scoreof 89.47% (very good) and student response results with an average score of86.45% (very good). Some suggestions from the experts include in theteaching material description section added with illustrations in the form ofdrawings or schemes; and equipped with concrete examples in accordancewith the contextual situation. While the suggestions from the students arealso in line with the advice of the expert team that is also equipped withconcrete examples to be more reproduced.